SU-8 Piezoresistive Microcantilever For Chemical Sensing Application - Lee, Kok Siong (2011)

(untitled)
In this research, the ultraviolet (UV) patternable polymer material, SU-8 with very low Young’s modulus compared to conventional silicon based material, is utilized as structural material for microcantilever to enhance the piezoresistive strain. In addition to that, a thorough Finite Element Analysis (FEA) has been carried out for SU-8 piezoresistive microcantilever under the surface stress loading to help in improving the piezoresistive strain when designing the cantilever sensor. The analysis result concluded that the SU-8 cantilevers for chemical sensing should have lower length to width (L/W) ratio for higher piezoresistive strain.